Cyclodextrin‐functionalized silica nanoparticles with dendrimer‐like spacers for enantioselective capillary electrochromatography. Issue 24 (15th October 2014) - Guo, Yujun; Qin, Weidong; Nilsson, Carol; Lichti, Cheryl; Liu, Huiling
<x xml:space="preserve">Abstract</x> In this report, β‐cyclodextrin (β‐CD)‐functionalized silica nanoparticles (SNPs) with dendrimer‐like spacers were synthesized by first grafting the SNPs with different generations of polyamidoamines (PAMAMs), followed by modifying the grafted SNPs with mono‐6‐deoxy‐(p‐tolylsulfonyl)‐β‐CD. The β‐cyclodextrin‐modified silica nanoparticle‐cored PAMAMs (SNP‐PAMAM‐β‐CDs) were studied as chiral pseudostationary phases for separating three racemic drugs, namely, chlorpheniramine, nefopam, and verapamil. The β‐CD‐functionalized SNPs with dendrimer‐like spacers were more enantioselective than native β‐CD, and the structures of the dendritic spacers were highly influential on the separation. In 20 mM NaH2PO4, addition of 4.00 mg/mL SNP‐G1.0‐β‐CD (corresponding to 1.12 mM β‐CD) could baseline separate the enantiomers of chlorpheniramine and nefopam, and introduction of 7.00 mg/mL SNP‐G0‐β‐CD (corresponding to 1.68 mM β‐CD) resulted in enantioseparation of the verapamil racemates. On the contrary, the enantiomers of nefopam and verapamil could not be resolved in the presence of 15 mM native β‐CD. Our results suggest that SNP‐PAMAM‐β‐CDs hold great promise for enantioselective separations.